2020
DOI: 10.1515/polyeng-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lamellar microstructure of retinoic acid loaded-matrixes on physicochemical properties, migration, and neural differentiation of P19 embryonic carcinoma cells

Abstract: In this study, retinoic acid loaded-PLGA-gelatin matrixes were prepared with both freeze-casting and freeze-drying techniques. Herein, the effect of unidirectional microstructure with tunable pores on release profile, cellular adhesion, migration, and differentiation was compared. Morphological observation determined that highly interconnected porous structure can be formed, but lamellar pore channels were observed in freeze-casting prepared constructs. The absorption ratio was increased, and the biodegradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Lee et al [33] developed a hydroxyapatite collagen calcium silicate-polydopamine (HCCS-PDA) biomaterial to repair critical size bone defects; they found that the flexural strength of HCCS-PDA was higher than that of HCCS after PDA modification. Ghorbani et al [28] found that the tensile strength and Young's modulus of polyvinyl alcohol /polyurethane -polyaniline matrices with PDA were increased, which is indicative of the potential of application processes in bone tissue engineering.…”
Section: Mechanical Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [33] developed a hydroxyapatite collagen calcium silicate-polydopamine (HCCS-PDA) biomaterial to repair critical size bone defects; they found that the flexural strength of HCCS-PDA was higher than that of HCCS after PDA modification. Ghorbani et al [28] found that the tensile strength and Young's modulus of polyvinyl alcohol /polyurethane -polyaniline matrices with PDA were increased, which is indicative of the potential of application processes in bone tissue engineering.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…Xi et al [28] reported that the membranes of porous polymers became smoother after poly(3,4-dihydroxyphenylalanine) coating. Conversely, poly(L-lactide-co-caprolactone)film surfaces transitioned from smooth to rough.…”
Section: Roughness and Morphologymentioning
confidence: 99%